Habitat features and long‐distance dispersal modify the use of social information by a long‐distance migratory bird. (11th August 2015) - Rushing, Clark S.; Dudash, Michele R.; Marra, Peter P.; Wunder, Michael
Summary The processes by which individuals select breeding sites have important consequences for individual tness as well as population‐ and community‐dynamics. Although there is increasing evidence that many animal species use information acquired from conspecics to assess the suitability of potential breeding sites, little is known about how the use of this social information is modified by biotic and abiotic conditions. We used an automated playback experiment to simulate two types of social information, post‐breeding public information and pre‐breeding location cues, to determine the relative importance of these cues for breeding site selection by a migratory songbird, the American redstart (Setophaga ruticilla). In addition, we used stable hydrogen isotopes to determine the dispersal status of individuals that responded to our experimental treatments and quantify whether long‐distance dispersers use different social cues to select breeding sites compared to philopatric individuals. We found that points that received pre‐breeding location cue treatments were signi cantly more likely to be settled by redstarts than control points that received no playback. However, we found no evidence the redstarts used post‐breeding public information gathered during one season to select breeding sites the following year. Breeding site habitat structure was also a strong predictor of settlement probability, indicating that redstarts modi ed the use of social information based on habitat cues. Furthermore, stable hydrogen isotope signatures from individuals that responded to location cue treatments suggest that long‐distance dispersers may rely more heavily on these cues than local recruits. Collectively, these results indicate that redstarts use multiple sources of information to select breeding sites, which could buffer individuals from selecting suboptimal sites when they breed in unfamiliar locations or when habitat quality becomes decoupled from social cues.